Performance Enhancement of Five Bus Power System Using Shunt Based FACTS Controllers - Jena, Ramakanta; Swain, Sarat Chandra; Chirantan, Shaswat; Dash, Ritesh (International Journal of Advances in Applied Sciences, 2021)
FACTS(Flexible AC Transmission System) a boost for grids, have the superior characteristics of grid flexibility,power quality improvement,long distance AC transmission & control series & shunt compensation.FACTS controllers have the inherent features of inject or absorb reactive power to/from the line at the time of requirement.These are synchronized by a bunch of power electronics based controllers.FACTS controllers are of series or shunt connected type or combination of both depending upon their connection with the transmission line.Generally these devices have the most reliable nature of enhancing the maximum power transfer capability from source end to load end.Because of this, FACTS controllers are most significantly used in recent days power system.In this paper shunt type of FACTS controller is taken for system performance analysis of a five bus system.FACTS devices considered here are SVC(Static Var Compensator) & STATCOM(Static Synchronous Compensator).Here,load flow analysis to be taken as the basic criteria for the study.Firstly,Load flow study has been conducted for an uncompensated five bus system & there by analyzing the stability limits in terms of voltage magnitude(p.u) and loss analysis in terms of overall real & reactive power losses.Then load flow study has been carried out for both the FACTS devices independently by incorporating them in to the five bus system.Also the optimal location of SVC & STATCOM is determined by installing at each bus separately & by considering the least possible losses and improved voltage profiles.A comparative study has been done here for these controllers in terms of enhancement of voltage stability and loss minimization & hence improvement of the power transfer capability.SVC & STATCOM both are of shunt FACTS controllers but they may differ in their functionality based on various system parameters in power system.The detailed performance analysis of an uncompensated & shunt compensated five bus system(SVC & STATCOM compensation) is investigated here.All the system performance study has been featured by using MATLAB/SIMULINK software.